Improved Operational Flexibility of the M2AC for Direct AC/AC Conversion - Anjana Wijesekera; Gregory J. Kish (IEEE Open Journal of Power Electronics)
The modular multilevel ac/ac converter (M2AC) is a recently proposed partial power processing topology for direct ac/ac conversion that can adjust voltage magnitudes and phase angles in single-frequency ac power systems, analogous to a power electronic autotransformer. However, prior studies have been limited to investigating only active power transfers and basic operating features. This article addresses this gap by proposing three operating flexibility enhancements for the M2AC: 1) accommodating practical power flow scenarios where independent control of active and reactive powers is needed, 2) eliminating large dc-link capacitors to realize a fully modular and scalable architecture, and 3) incorporating full fault blocking akin to ac circuit breaker functionality. The fundamental operating principles and fault-blocking characteristics are thoroughly studied for different M2AC design variants, and a comparative analysis is conducted to quantify potential semiconductor savings in comparison to the back-to-back modular multilevel converter as a benchmark. Converter controls incorporating active and reactive power flow management and internal capacitor voltage cell balancing are developed. The M2AC’s steady-state and transient operation and fault-blocking capabilities are validated through simulation studies and further confirmed by experimental tests using a laboratory-scale 250 Vpk, 1 kVA prototype.